Kearifan Lokal Masyarakat Nias - Amstrong Harefa; Haris Joshua Hia; Antonius Zai; Penataran Lase; Perdamaian Zega; Alvian Putri Gulo; Asniar Windi Tafonao; Yarniwa Gulo; Daria Darmawati Gea; Ardius Zai (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2026)
This study examines the local wisdom of the Nias people by placing it within the framework of pluralism, social harmony, and cultural values passed down from generation to generation. The Nias people are a pluralistic community ethnically and religiously, consisting of the Nias tribe and various immigrant groups such as Chinese, Batak, Padang, Javanese, as well as adherents of Protestant Christianity, Catholicism, Islam, and Buddhism. This plurality is integrated in a social system supported by local wisdom such as banua-fatalifusöta, emali dome si so ba lala, and sebua ta’ide’ide’ö which play a role in maintaining social cohesion, tolerance, and conflict resolution within the family. This study uses a qualitative method with a historical-normative approach through literature and document analysis, in order to trace the historical construction and normative meaning of these local wisdom values. The results show that the local wisdom of the Nias people functions as an effective social mechanism for maintaining inter-religious and inter-ethnic harmony, and makes a significant contribution to the creation of social-communitarian stability that is rarely found in other plural societies in Indonesia. This study strengthens the understanding that traditional values and local wisdom are determining factors in the formation of social harmony in Nias society.